Horizontally Acquired nrDNAs Persist in Low Amounts in Host Hordeum Genomes and Evolve Independently of Native nrDNA - Krak, Karol; Caklová, Petra; Kopecký, David; Blattner, Frank R.; Mahelka, Václav (Frontiers in Plant Science, 2021)
Nuclear ribosomal DNA (nrDNA) has displayed extraordinary dynamics during the evolution of plant species. However, the patterns and evolutionary significance of nrDNA array expansion or contraction are still relatively unknown. Moreover, only little is known of the fate of minority nrDNA copies acquired between species via horizontal transfer. The barley genus Hordeum (Poaceae) represents a good model for such a study, as species of section Stenostachys acquired nrDNA via horizontal transfer from at least five different panicoid genera, causing long-term co-existence of native (Hordeum-like) and non-native (panicoid) nrDNAs. Using quantitative PCR, we investigated copy number variation (CNV) of nrDNA in the diploid representatives of the genus Hordeum. We estimated the copy number of the foreign, as well as of the native ITS types (ribotypes), and followed the pattern of their CNV in relation to the genus’ phylogeny, species’ genomes size and the number of nrDNA loci. For the native ribotype, we encountered an almost 19-fold variation in the mean copy number among the taxa analysed, ranging from 1689 copies (per 2C content) in H. patagonicum subsp. mustersii to 31342 copies in H. murinum subsp. glaucum. The copy numbers did not correlate with any of the genus’ phylogeny, the species’ genome size or the number of nrDNA loci. The CNV was high within the recognised groups (up to 13.2× in the American I-genome species) as well as between accessions of the same species (up to 4×). Foreign ribotypes represent only a small fraction of the total number of nrDNA copies. Their copy numbers ranged from single units to tens and rarely hundreds of copies. They amounted, on average, to between 0.1% (Setaria ribotype) and 1.9% (Euclasta ribotype) of total nrDNA. None of the foreign ribotypes showed significant differences with respect to phylogenetic groups recognised within the sect. Stenostachys. Overall, no correlation was found between copy numbers of native and foreign nrDNAs suggesting the sequestration and independent evolution of native and non-native nrDNA arrays. Therefore, foreign nrDNA in Hordeum likely poses a dead-end by-product of horizontal gene transfer events.